2019
DOI: 10.1002/we.2333
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of ice formations on wind turbine blades and power production losses due to icing

Abstract: Prediction of ice shapes on a wind turbine blade makes it possible to estimate the power production losses due to icing. Ice accretion on wind turbine blades is responsible for a significant increase in aerodynamic drag and decrease in aerodynamic lift and may even cause premature flow separation. All these events create power losses and the amount of power loss depends on the severity of icing and the turbine blade profile. The role of critical parameters such as wind speed, temperature, liquid water content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 19 publications
1
23
0
1
Order By: Relevance
“…Ice accumulation is a common and serious phenomenon that exists in numerous industrial fields such as electricity transportation, wind turbine and air conditioning [1][2][3]. The ice accretion may cause the failure of conductors, decrease the efficiency of air conditioning and even cause the system shutdown, which would pose a huge energy consumption and potential safety hazard [4,5]. Therefore, developing an effective and reliable method to reduce ice accumulation is of great practical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Ice accumulation is a common and serious phenomenon that exists in numerous industrial fields such as electricity transportation, wind turbine and air conditioning [1][2][3]. The ice accretion may cause the failure of conductors, decrease the efficiency of air conditioning and even cause the system shutdown, which would pose a huge energy consumption and potential safety hazard [4,5]. Therefore, developing an effective and reliable method to reduce ice accumulation is of great practical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Wind turbine blade ice accretion, which occurs primarily near the leading edge, has demonstrated negative effects on blade performance, including reduced power outputs, surface erosion, and sudden blade failures and damage [2]. The aerodynamic impact of ice accretion, particularly related to changes in the airfoil and blade geometries due to ice formation, has been widely studied in correlation with wind turbine performance and power outputs [3][4][5][6][7][8][9][10][11][12][13][14]. A number of recent studies have also experimentally investigated the progression of ice accretion on wind turbine airfoils, including changes in the shape, distribution, and properties of ice that occur during this process [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…To maintain the rotation of a vertical axis rotating rig, Han et al 5 found that the torque requirement increased 70% under severe icing conditions. Recently, Yirtici et al 6 predicted 17% power loss for a NREL 5‐MW wind turbine during icing conditions. In addition, icing on the airfoil leads to measurement errors due to ice accretion on sensors and increased mechanical loads, which can ultimately lead to mechanical failures, electrical failures, changes in material properties and safety issues related to ice being thrown from the rotor blades 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of the contaminations agrees qualitatively well with ice geometries found in the literature. 6,8,15 However, ice feathers or rivulets located downstream of the leading edge are not present in the geometries used in the present study. The type C contamination geometry is horn-like.…”
mentioning
confidence: 99%